Liquid Biofertilizer Made from Fermented Egg Shells, Fish Scales, and Chicken Feathers as A Plant Growth Stimulator Alternative to Chemical Fertilizer - Ramadhan, Muhammad Nadhif Rasendriya; Arfarifki, Muhammad Farel; Khalisa, Fachira; Khalief, Raffi; Fadhil, Muhammad; Sari, Widya; Asiandu, Angga Puja (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
As agricultural sectors rise due to increased human population, the demand for chemical fertilizer is also uplifted. However, the excessive use of chemical fertilizers reduces soil quality and natural properties. To address these issues, an alternative eco-friendly biofertilizer is needed. Here, we developed a liquid biofertilizer called ESSIK to substitute hazardous chemical fertilizers. It is made from environmentally friendly waste materials—including chicken feathers, egg shells, and fish scales—which are repurposed to provide vital nutrients for plant growth. Egg shells contain calcium useful in the synthesis of plant enzymes, fish scales contain calcium and phosphorus which play a role in accelerating fruit ripening, and chicken feathers contain high protein which can be a source of amino acids. These components were first fermented using effective microorganisms (EM4) to break down complex polymers into forms more readily absorbed by plants. The fermented biofertilizer was tested using mung bean (Vigna radiata) with concentrations of 0%, 5%, 10%, 20%, and 100%, and a positive control of 5% EM4. Based on the study, 20% was the best formulation to support the growth of mung bean (V. radiata) with a length of more than 41 cm, 16 leaves, and 9 stalks. Also, the leaf's length was approximately 6,6 cm, width 3,8 cm, with a healthy-green appearance. These findings suggest that it has significant potential as an eco-friendly and sustainable biofertilizer alternative to chemical fertilizers, promoting robust plant growth while contributing to waste recycling and environmental conservation for a better future.